Identification of Flowering Regulatory Networks and Hub Genes Expressed in the Leaves of Elymus sibiricus L. Using Comparative Transcriptome Analysis - Zheng, Yuying; Wang, Na; Zhang, Zongyu; Liu, Wenhui; Xie, Wengang (Frontiers in Plant Science, 2022)
Flowering is a significant stage from vegetative growth to reproductive growth in higher plants, which impacts the biomass and seed yield. In order to reveal the flowering time variations and identify the flowering regulatory networks and hub genes in Elymus sibiricus, we measured the booting, heading, and flowering times of 66 E. sibiricus accessions. The booting, heading, and flowering times varied from 136 to 188 days, 142 to 194 days, and 148 to 201 days, respectively. The difference in flowering time between the earliest- and the last-flowering accessions was 53 days. Furthermore, transcriptome analyses were performed at the three developmental stages of six genotypes with contrasting flowering times. A total of 3,526 differentially expressed genes (DEGs) were predicted and 72 candidate genes were identified including transcription factors, known flowering genes, and plant hormone-related genes. Among them, four candidate genes LATE), GA2OX6, FAR3, and MFT1 were significantly up-regulated in late-flowering genotypes. LIMYB, PEX19, GWD3, BOR7, PMEI28, LRR, and AIRP2 were identified as hub genes in the turquoise and blue modules by weighted gene co-expression network analysis (WGCNA). A single nucleotide mutation (SNP) of LIMYB found by multiple sequence alignment may cause late flowering. The expression pattern of flowering candidate genes was verified in eight flowering promoters (CRY, COL, FPF1, Hd3, GID1, FLK, VIN3, and FPA) and four flowering suppressors (CCA1, ELF3, Ghd7, and COL4) under drought and salt stress by qRT-PCR. The result suggested that drought and salt stress activated the flowering regulation pathways to some extent. The findings of the present study lay a foundation for the functional verification of flowering genes and breeding of new varieties of early- and late-flowering in E. sibiricus.